Analisis Kinerja Realisasi Anggaran Pendapatan dan Belanja Daerah Pada Pemerintahan Kabupaten Magelang Tahun 2018-2022 - Najla Aulia Nur Ramadhianti; Sherindea Permata Agita; Meylisa Eka Putri; Yusni Kartika Cahyaningtyas; Herlina Manurung (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
With regard to the ratio of fiscal decentralization, effectiveness of PAD, regional financial efficiency, and compatibility of regional spending, this study intends to analyze the regional financial performance of Magelang Regency. This study examines the financial position of the Magelang Regency Government from 2018 to 2022 using quantitative descriptive analysis. According to the decentralization degree ratio analysis, the Magelang Regency Government Budget generates high revenue figures, with an average decentralization rate of 97.50% between 2018 and 2022. According to the variance analysis, the expenditure performance of the Magelang district government in general can control the budget, so that it can achieve an average surplus of Rp. 755,037,801,786.6 (remaining after budget calculation) between 2018 and 2022. According to the variance analysis, the expenditure performance of the Magelang district government in general can control the budget, so that it can achieve an average surplus of Rp. 755,037,801,786.6 (remaining after budget calculation) between 2018 and 2022. The Magelang Regency Government spent 93.09% of its total budget on direct expenditures in 2018–2022, while only 1.39% was allocated for indirect expenditures. Based on the analysis of expenditure efficiency, the efficiency level of the Magelang Regency Government for the 2018–2022 fiscal year can be assessed as efficient, with an average of 98.85%. Annual operating expenses for the short term are still prioritized by the Magelang Regency Government over capital expenditure for long-term growth in its regional budget.